2016
DOI: 10.1038/srep27080
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus VvhA induces autophagy-related cell death through the lipid raft-dependent c-Src/NOX signaling pathway

Abstract: VvhA, a virulent factor of Vibrio (V.) vulnificus, induces acute cell death in a destructive manner. Autophagy plays an important role in cell death, but the functional role of VvhA in autophagy-related cell death has not been elucidated yet. We found that rVvhA significantly increased LC3 puncta formation and autophagic flux in promoting the cell death of human intestinal epithelial Caco-2 cells. The cell death induced by rVvhA was independent of lysosomal permeabilizaton and caspase activation. rVvhA induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 60 publications
4
41
0
1
Order By: Relevance
“…Intracellular ROS detection was described in previous reports [39]. ROS was detected by using DCF-DA, which is a fluorescence-based probe for ROS detection.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS detection was described in previous reports [39]. ROS was detected by using DCF-DA, which is a fluorescence-based probe for ROS detection.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrio (V.) vulnificus is a pathogenic marine bacterium associated with foodborne illnesses, often causing gastroenteritis, septicemia, and diarrhea [1]. Infection with V. vulnificus is cytotoxic to host cells, and its virulence is mediated by secreted cytotoxins and enzymes, such as VvhA, MARTX, VvpE, and VvpM [1][2][3][4][5][6]. VvhA is one of the most potent pore-forming cytotoxins capable of killing mice at sub-µg levels, and it plays a crucial role in the pathogenesis and dissemination of V. vulnificus by facilitating intestinal paracellular permeabilization [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with V. vulnificus is cytotoxic to host cells, and its virulence is mediated by secreted cytotoxins and enzymes, such as VvhA, MARTX, VvpE, and VvpM [1][2][3][4][5][6]. VvhA is one of the most potent pore-forming cytotoxins capable of killing mice at sub-µg levels, and it plays a crucial role in the pathogenesis and dissemination of V. vulnificus by facilitating intestinal paracellular permeabilization [2]. Recent studies have suggested that recombinant (r) VvhA stimulates the mitochondrial apoptotic machinery through the production of intracellular reactive oxygen species (ROS) derived from NADPH oxidase 2 (NOX2) located on membrane lipid rafts, thereby governing the PKC, MAPK, and NF-κB signaling pathways during the infection of host cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…V. parahaemolyticus O1:Kuk strain may potentially cause human illness, because this strain is closely related with strain O3:K6 which was associated with quite a number of Asian outbreaks (Depaola et al, 2003). V. vulnificus MLT1009 has VvhA (virulent factor of V. vulnificus) gene that induces autophagy-related cell death (Song et al, 2016). Each was cultivated overnight in Tryptic Soy Broth, (TSB, Carolina Biological Supply Co.) supplemented with 2% additional NaCl at 37 • C, and washed twice with normal saline (0.85% NaCl) buffer.…”
Section: Fish and Rearing Conditionmentioning
confidence: 99%